Avaliação da motivação, funções executivas e indicadores táticos em atletas de futebol da categoria sub-20 em uma competição federada - Maurício Jose de Souza Filho (2016)
This study aimed to: (a) compare the dimensions of intrinsic and extrinsic motivation and demotivation of U-20 soccer athletes; (b) to compare the self- determination index, the executive function measures and the tactical indicators between the athletes that play in big and small clubs; (c) to propose normative tables for U-20 athletes in relation to the variables: self- determination index, three measures of executive functions and seven tactical indicators; (d) to verify the association between the status (big or small) of U-20 soccer clubs and the number of athletes with low and high scores of the self- determination index, in the executive function measures and of the tactical indicators. 104 athletes from six soccer clubs participating in the U-20 Minas Gerais state competition (2015) were evaluated. For match analysis, the sample was composed of 9.310 individual attacking actions, realized in 23 matches of the competition. The following instruments were used: (a) the questionnaire of demographic data, (b) the Sports Motivation Scale (SMS), (c) the Corsi Block test, (d) the five digit test and (e) tactical indicators: number of received balls (NR), number of contacts with the ball (NCT), amount of runner variation (NVC), speed of ball transmission (VTB), number of conquered balls (NC), total of played balls (BJT). The results showed that the general reliability of the instruments was considered acceptable for the SMS (=0,88), Corsi Block (=0,69) and the Five Digit Test (=0,78). The minimal value of accordance between the observators were k=0,896 (epm=0,060), indicating acceptable reliability. It was identified that the U-20 soccer athletes present higher levels of intrinsic motivation, followed by extrinsic motivation and low levels of demotivation, with large effect (ES>0.5). The results point towards higher scores of working memory in athletes that play in big clubs, compared to athletes that play in small clubs. It was also found that there was an association between the status of clubs (big or small) of U-20 soccer and the number of athletes with low and high scores for the measurement of working memory. It is concluded that the U-20 soccer players presented a self-determined motivation profile. Regarding the executive functions, it is concluded that the athletes of big clubs excel athletes from small clubs only in relation to working memory, indicating that an athlete playing in a big club seems to be associated with a greater ability in memorizing visual information. In summary, according to the results of this study, the athletes in the U-20 Minas Gerais state competition who play in big clubs and small clubs are similar in the motivational point of view, executive functions (inhibitory control and cognitive flexibility) and tactical aspects when playing at home